TOPICAL DRUG DELIVERY FOR EFFECTIVE TREATMENT OF BACTERIAL INFECTIONS OF THE ANTERIOR SEGMENT OF THE EYE - Abd El-bary, Ahmed; Kamal Ibrahim, Howida; Saeed Hazaa, Balqees (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Anterior parts of the eye are susceptible to infections caused by different bacterial species. The use of suitable therapeutic measures in case of ocular infections can be sight saving. The appropriate therapy depends on selecting the right antibacterial as well as an efficient drug delivery system. Despite their accessibility, topical delivery of the selected antibiotic into the anterior ocular parts is still a challenging issue due to the complex nature of the eye. Ocular therapy would be significantly improved by modifying the physicochemical properties of the drug and by prolonging its pre-corneal residence time. This review will help pharmaceutical formulators to identify different parts of the eye and the corresponding bacterial infections, ocular barriers to drug delivery, and general consideration when formulating ocular drug delivery systems for the treatment of eye infections.